The Effect of Return on Assets, Firm Size and Risk Management on Firm Value with Good Corporate Governance as a Mediation Variable (Empirical Study of Sharia Commercial Banks 2015-2019) - Sari, Eka Purnama; Rokhmawati, Andewi; Halim, Edyanus H (Program Pascasarjana, Universitas Riau, 2021)
The implementation of Good Corporate Governance aims to create added value for all interested parties through improved management performance to increase corporate value and encourage the creation of an efficient, transparent, and following statutory regulations. The research objectives in conducting this research are to analyze and determine the Return on Assets, Company Size, Risk Management, and Good Corporate Governance, which affect the Company's Value through Good Corporate Governance. The results of this study found that return on assets has a significant positive effect on good corporate governance, firm size has a significant positive effect on good corporate governance, risk management has a significant positive effect on good corporate governance, good corporate governance has a significant positive effect on firm value, return on assets has a significant positive effect on firm value. significant positive effect on firm value, firm size has a significant positive effect on firm value, risk management has a significant positive effect on firm value.